2012
DOI: 10.6061/clinics/2012(06)13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous and interval exercise training on the PETCO2 response during a graded exercise test in patients with coronary artery disease

Abstract: OBJECTIVE:The purpose of this study was to evaluate the following: 1) the effects of continuous exercise training and interval exercise training on the end-tidal carbon dioxide pressure (PETCO2) response during a graded exercise test in patients with coronary artery disease; and 2) the effects of exercise training modalities on the association between PETCO2 at the ventilatory anaerobic threshold (VAT) and indicators of ventilatory efficiency and cardiorespiratory fitness in patients with coronary artery disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 20 publications
3
49
0
7
Order By: Relevance
“…From all reviewed studies, 4 showed a superior effect of HIIT over CAET on VȮ 2 peak and prescribed long intervals (4-min intervals at 80-95% HRpeak) [29,[45][46][47]. Similar benefits were found for HIIT versus CAET for VĖ=VĊO 2 slope, oxygen uptake efficiency slope [43], partial pressure of end-tidal CO 2 [48], coronary atheroma and plaque characteristics [44] and quality of life [49]. Furthermore, some studies evaluated HIIT versus CAET for effects on blood pressure [43,47,[50][51][52], HR recovery and HR variability [51] as well as systolic function and systolic volumes [29,49] and found no effects of training on these variables.…”
Section: Hiit Versus Caet Programssupporting
confidence: 76%
“…From all reviewed studies, 4 showed a superior effect of HIIT over CAET on VȮ 2 peak and prescribed long intervals (4-min intervals at 80-95% HRpeak) [29,[45][46][47]. Similar benefits were found for HIIT versus CAET for VĖ=VĊO 2 slope, oxygen uptake efficiency slope [43], partial pressure of end-tidal CO 2 [48], coronary atheroma and plaque characteristics [44] and quality of life [49]. Furthermore, some studies evaluated HIIT versus CAET for effects on blood pressure [43,47,[50][51][52], HR recovery and HR variability [51] as well as systolic function and systolic volumes [29,49] and found no effects of training on these variables.…”
Section: Hiit Versus Caet Programssupporting
confidence: 76%
“…They involved assessments of HIIT versus MCT for patients with CAD, including metabolic syndrome (n=10) (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), and CHF, including diastolic dysfunction (n=11) (15,16,(28)(29)(30)(31)(32)(33)(34)(35)(36). In the studies shown in Tables 1 and 2, although the VO2peak was not necessarily the primary endpoint, we presented the VO2peak at baseline and the percentage increase in the VO2peak during the exercise period in order to compare the two groups.…”
Section: Benefits Of Hiitmentioning
confidence: 99%
“…Variables other than the VO2peak, in which HIIT is superior to MCT, are summarized in Table 3 (15,16,21,24,26,28,31,32,34).…”
Section: Rcts Comparing Central and Peripheral Adaptations In Hiit Anmentioning
confidence: 99%
“…However, increases in VO 2max of between 10 and 20% are more typical when sedentary individuals are subjected to a specific period of aerobic exercise training. Moreover, previous investigations have demonstrated an increase in aerobic capacity after aerobic exercise training in patients with different comorbidities such as cardiovascular [9,10] and autoimmune diseases [36].…”
Section: Exercise Training and Aerobic Capacitymentioning
confidence: 99%
“…Importantly, aerobic exercise training has been recommended as non-pharmacological treatment for patients with a range of different comorbidities [9,10]. In this regard, recent evidence suggests that exercise training has direct effects on improving aerobic capacity and physical function in SLE patients [3,11,12].…”
Section: Introductionmentioning
confidence: 99%